Energy-effective and low-cost carbon capture from point-sources enabled by water-lean solvents - Jiang, Yuan; Mathias, Paul M.; Zheng, Richard F.; Freeman, Charlies J.; Barpaga, Dushyant; Malhotra, Deepika; Koech, Phillip K.; Zwoster, Andy; Heldebrant, David J. (Journal of cleaner production, 2023)
Aqueous amines, as the most mature carbon capture technology, are subject to high energy and cost penalties due to the large water content in their formulations. Emerging technologies are in demand to enable a transition to a low-carbon global economy. However, rigorous process modeling and techno-economic analyses are limited for emerging carbon capture technologies. Here, four CO2-Binding Organic Liquids (CO2BOLs), all water-lean solvents were presented as promising options towards energy-effective and low-cost carbon capture from point sources. Rigorous solvent property and process models were developed in Aspen Plus for a coal-fired power plant with CO2BOL-based carbon capture unit. Techno-economic analyses were conducted in 2018 US pricing basis. The results suggest that water-lean formulations can minimize water condensation and vaporization, leading to a 36% energy saving compared with aqueous amines. Indeed, these CO2BOLs can capture up to 97–99% CO2 from coal fired plant. The estimated carbon capture cost is about $40/tonne CO2 at 90–97% carbon capture rate, about 12–23% less expensive than the conventional aqueous amine technology. The comparison between these CO2BOLs showed that in addition to vapor liquid equilibrium and kinetics (key properties for aqueous solvents), viscosity, volatility, and hydrophobicity, also have strong impacts on the performance of water-lean solvents. The methods presented in this work can be used to evaluate other emerging carbon capture technologies, while the results linking costs and performance of carbon capture solvents with their properties. Further, this work identifies research directions and targets for further reductions in total costs of capture from either cost or energy perspectives for these leading water-lean solvents. [Display omitted] •Developed process models for four water-lean point-source carbon capture solvents.•Conducted techno-economic comparison and provided cost breakdowns for different solvents.•Water-lean solvents can enable up to 36% energy saving for carbon capture.•Water-lean solvents can enable about 12–23% reduction in carbon capture cost.